The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares - Welter, Saskia; Bracho-Nuñez, Araceli; Mir, Celine; Zimmer, Ina; Kesselmeier, Jürgen; Lumaret, Roselyne; Schnitzler, Jörg-Peter; Staudt, Michael (Tree Physiology, 2012)
Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively. In a common garden experiment, we examined the terpene emission capacities, terpene synthase (TPS) activities and nuclear genetic markers in 52 trees of these three oak species. All but one of the Q. suber and Q. canariensis trees were found to be genetically pure, whereas most Q. afares trees possessed a mixed genotype with a predominance of Q. suber alleles. Analysis of the foliar terpene emissions and TPS activities revealed that all the Q. canariensis trees strongly produced isoprene while all the Q. suber trees were strong monoterpene producers. Quercus afares trees produced monoterpenes as well but at more variable and significantly lower rates, and with a monoterpene pattern different than that observed in Q. suber. Among 17 individuals tested, one Q. afares tree emitted only an insignificant amount of terpenes. No mixed isoprene/monoterpene emitter was detected. Our results suggest that the capacity and pattern of volatile terpene production in Algerian Q. afares populations have strongly diverged from those of its parental species and became quantitatively and qualitatively reduced, including the complete suppression of isoprene production.
10.1093/treephys/tps06910.1093/treephys/tps069
Keywords: Algerian oak; allozyme polymorphism; chemo-taxonomy; chemotype; Cork oak; isoprene synthase; isoprenoid; speciation